ASSOCIATION OF ANTI-CYCLIC CITRULLINATED PEPTIDE ANTIBODY IN A SAMPLE OF ADULT PATIENTS WITH PSORIASIS AND PSORIATIC ARTHROPATHY - Al-bedri, Khudair; Mahmood, Zainab A; Hussein Sadeq, Aqeel (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Psoriatic arthritis (PsA) is a chronic inflammatory arthropathy commonly associated with psoriasis, a large number of patients with PsA that has persistent inflammation may develop progressive joint damage and disability and have reduced life expectancy. This study aims to determine the associations of anti-cyclic citrullinated peptide (CCP) antibodies in adult patients with psoriasis and PsA. Methods: A case–control study was conducted at Baghdad teaching hospital, Units of Rheumatology and Dermatology, during the period from December 2016 to April 2017 including three groups; 40 patients with psoriasis, 40 patients with PsA fulfilling the CASPAR classification criteria, and 40 healthy control persons. Results: Two patients with psoriasis (5%) and 10 patients with PsA (25%) were seropositive for anti-CCP antibodies (ACPA). Healthy controls were negative for anti-CCPA. Regarding ACPA positivity, a significant difference was found between those three studied groups (p<0.001) and there was a significant difference between positive and negative ACPA in PsA patients regarding disease activity score (p=0.044). Conclusion: Positive ACPA were found more significant with PsA than in patients with psoriasis as well as associated with higher disease activity.